Discovery of a Uracil-Derived Small Organic Ligand with Cytotoxic Effect on Human PC-3 Cell Lines via Apoptosis - Poslu, Ayse Halic; Balaban, Rumeysa; Nalbantsoy, Ayse; Ertik, Onur; Cecener, Gulsah; Koz, Omer; Koz, Gamze (Wiley-V C H Verlag Gmbh, 2024)
A series of novel 6-amino-5-salicylidene uracils (1-19) were efficiently synthesized from the condensation reaction of 5,6-diamino-1,3-dimethyluracil with substituted salicylaldehydes. The structural characterization of the compounds was performed with spectroscopic methods and elemental analysis. All compounds were evaluated for their in vitro cytotoxic activity against PC-3 (human prostate adenocarcinoma), A549 (human alveolar adenocarcinoma) and SHSY-5Y (human neuroblastoma) cancer cell lines. 3,5-di-tert-Butylsalicylaldehyde derived salicylideneuracil (6ASU-8) showed promising cytotoxic activity against PC-3 cells with an IC50 value of 1.53 +/- 1.01 mu M, compared to doxorubicin, which had an IC50 value of 3.77 +/- 1.34 mu M. 6ASU-8 induced cell cycle arrest at the G2/M phase and promoted apoptosis in PC-3 cells (p<0.05*). Molecular docking results supported the experimental data, indicating that 6ASU-8 is more effective than doxorubicin. Additionally, in silico ADME analysis revealed that 6ASU-8 possesses acceptable predictive physicochemical properties.
Keywords: Uracil; Cytotoxicity; PC-3; Apoptosis; Molecular docking